A sense of health and coherence in young rural schoolchildren in Sweden. Issue 1 (1st January 2021) - Randell, Eva; Udo, Camilla; Warne, Maria
ABSTRACT: Background : Little is known about how younger schoolchildren in a rural setting experience their sense of coherence (SOC), how they think and reason about health and what they perceive as important to achieve health goals. This study aimed to investigate children's SOC and their health perceptions.Method : In this mixed-method study 94 children (8-12 years) from three rural schools answered several questionnaires: The Child-SOC (CSOC), Positive Health Scale (PHS) and Cantril's ladder of life scale. Another 23 children (of 94) participated in four focus group interviews. Thematic analysis was used to identify themes from the interview transcripts.Results : High SOC was reported by 48% of the boys and 22% of the girls. However, no significant gender differences were found. Four themes were generated from the qualitative analysis: Understanding health, Managing health, Doing bodily health and Socialising health. Both younger and older children had a holistic view of health in which health was seen as an individual's living habits in which social contacts mattered.Conclusion : In a rural context children need to adapt to activities that exist in their immediate environment. Thus, activities during school hours can be an important complement in health promotion.